Quality requirements in natural enemies used for inoculative release: practical experience from a successful biological control programme - Neuenschwander, Peter; Haug, T.; Ajounu, O.; Davis, H.; Akinwumi, B.; Madojemu, E. (Wiley, 1989)
During the past six years, the South-American encyrtid wasp Epidinocarsis lopezi (De Santis) was released from the ground and from the air in about 100 areas in Africa for the biological control of the cassava mealybug (CM) Phenacoccus manihoti Mat.-Ferr. It was established in all release sites and, in 1988, occurred in 18 African countries over 1.5 mio. km2. Its efficiency in permanently reducing CM populations has been documented. E. lopezi was reared on its original host plant, cassava, and on the original insect host, the CM. Rearing methods for plants, CM, and E. lopezi were developed in the course of the actual production of parasitoids for release. Continuous production without bottlenecks was assured by >50 rearing units with potted plants and by large mechanized cages with hydroponic cultures, where cassava, insect host and parasitoid were reared in the same unit. Timing of parasitoid infestation and inoculum size were improved through in-depth biological and ecological studies. Host instar preference, host feeding and other nutritional requirements, mutilation of hosts, low reproductive capacity, superparasitism, and developmental time were taken into account for efficient rearing, storage, and transport. The successful establishment of E. lopezi, its spread, and efficiency in Africa attest to the production of sufficient numbers of wasps of high quality. Insect and plant studies, technology development, and careful supervision contributed to good quality which, in inoculative releases, takes precedence over high numbers.